The Organization of the Educational Processin the Legal Clinic - Dmitrii N. Polyakov (Сибирское юридическое обозрение, 2017)
In this article, the Author reveals the need to develop a special training course for the legal clinic, which should give students the opportunity to learn the basic skills and analytical thinking necessary to provide quality legal services. In addition, the article presents a number of organizational aspects of working with clients of the legal clinic, which give an overall picture of the competent and well-founded construction of the clinical educational process.